(3PcQi GdTjYI aj CMcGe GdTQjYIs - (3GdYGedj, GdLRjfj, CHh YHO Gddg, GdTgjO GdSYjO, eMeO Hf ecj Hf CMeO Hf MGeO, J(B786(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj TQY GdESdGe aSgd TQGFYg ddhGQOjf(B...(3CeG HYO agPG cJGH PcQi GdTjYI(B...(3ChQOJ ajg eG UOQ Yf SjO GdeQSdjf ef QhGjI GdeYUhejfs
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG(B: (3GdYbhO hgj UjZI eTQhWI HGKfjf hdh JbOjQG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B731s
(3GdPQjYI(B:(3L(B10(3,U(B31(3,Qbe(B221s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis